HSBC bank and Irish National Lottery among latest DDoS victims. (February 2016) - Unknown
Abstract : As high-profile government and commercial targets fall victim to Distributed Denial of Service (DDoS), Arbor Networks said it had registered what it claimed is the largest-ever DDoS attack, coming in at 500Gbps. As part of its annual 'Worldwide Infrastructure Security Report', the firm said that other attacks were witnessed at 450Gbps, 425Gbps and 337Gbps.